Fort CnoX: Protecting Bacterial Proteins From Misfolding and Oxidative Damage - Dupuy, Emile; Collet, Jean-François (Frontiers in Molecular Biosciences, 2021)
How proteins fold and are protected from stress-induced aggregation is a long-standing mystery and a crucial question in biology. Here, we present the current knowledge on the chaperedoxin CnoX, a novel type of protein folding factor that combines holdase chaperone activity with a redox protective function. Focusing on Escherichia coli CnoX, we explain the essential role played by this protein under HOCl (bleach) stress, discussing how it protects its substrates from both aggregation and irreversible oxidation, which could otherwise interfere with refolding. Finally, we highlight the unique ability of CnoX, apparently conserved during evolution, to cooperate with the GroEL/ES folding machinery.